Utilization of Stem Cells in Alginate for Nucleus Pulposus Tissue Engineering. (May 2014) - Huang, B.; Wang, H.; Zhou, Y.; Liu, L.; Liu, M.; Wang, J.; Li, C.; Zhang, Z.; Chu, T.; Xiong, C.
Introduction: In a general view of anatomy, intervertebral disc is composed of three parts: annulus fibrosus, nucleus pulposus (NP), and cartilage endplate. Recently, several types of stem cells were successfully isolated from these corresponding regions, but up to now, no research was performed about which kind of stem cells is the most efficient candidate for NP tissue engineering or for stem cell-based disc regeneration therapy. Materials and Methods: In this study, we compared the regenerative potentials of the above-mentioned three kinds of disc-derived stem cells with that of the classic bone marrow (BM)-mesenchymal stem cells (MSCs) in a rabbit disc degeneration model. By magnetic resonance imaging (MRI), X-ray, histology, and so on. Results: We found that cartilage endplate-derived stem cells (CESCs) showed superior capacity compared with the annulus fibrosus-derived stem cells (AFSCs), nucleus pulposus-derived stem cells (NPSCs), and BM-MSCs ( p < 0.05); in addition, when comparing the CESC group with the normal control group, there existed no statistical difference in X-ray ( p >0.05). Those results demonstrated that the CESC-seeded alginate construct performed the most powerful ability for NP regeneration, while AFSCs showed the most inferior potency, NPSCs and BM-MSCs had similar regenerative capacity and located in the middle. Conclusion: Our study showed that CESCs might act as an efficient seed cell source for NP tissue engineering, which paved a new way for the biological solution of disc degeneration diseases. Disclosure of Interest None declared